P1 plasmid replication: initiator sequestration is inadequate to explain control by initiator-binding sites. - Pal, S K (1988)
The unit-copy plasmid replicon mini-P1 consists of an origin, a gene for an initiator protein, RepA, and a control locus, incA. Both the origin and the incA locus contain repeat sequences that bind RepA. It has been proposed that the incA repeats control replication by sequestering the rate-limiting RepA initiator protein. Here we show that when the concentration of RepA was increased about fourfold beyond its normal physiological level from an inducible source in trans, the copy number of a plasmid carrying the P1 origin increased about eightfold. However, when the origin and a single copy of incA were present in the same plasmid, the copy number did not even double. The failure of an increased supply of RepA to overcome the inhibitory activity of incA is inconsistent with the hypothesis that incA inhibits replications solely by sequestering RepA. We propose that incA, in addition to sequestration, can also restrain replication by causing steric hindrance to the origin function. Our proposal is based on the observation that incA can bind to a RepA-origin complex in vitro.